The role of demographics in occupational stress and well being - Halbesleben, Jonathon R. B.; Perrewé, Pamela L.; Rosen, Christopher C. (Emerald, 2014)
This peer-reviewed series promotes theory and research in the expanding area of occupational stress, health and well being. Each volume of this series focuses on a particular topic, allowing authors and readers in that area to critically explore the cutting edge work from their discipline. Interest in organizational demography spans several decades (e.g., Pfeffer, 1983). However, in much of the contemporary research on occupational stress and well being, demographic factors such as gender, age, and race/ethnicity are evident in the background and controlled in statistical analysis. In this volume, we ask whether that should be the case and the extent to which those demographics impact our experience of stress and well being. Topics for this volume include age, occupational strain, and well being using a person-environment fit perspective; race, stress, and well being in organizations; gender facades, biological sex, and gender role stereotypes in the workplace; age, resilience, well being, and positive work outcomes; conceptual/theoretical issues related to religion and stress/well being; and sex and sexual orientation on occupational stress and well being.
Keywords: Job stress.; elektronické knihy; electronic books